Statistical Theory of Certain Distribution Functions in MHD Turbulent Flow for Velocity and Concentration Undergoing A First Order Reaction in a Rotating System (Bangladesh Journal of Scientific and Industrial Research, 2011)
Bangladesh J. Sci. Ind. Res. 46(1), 54-59, 2011